The role of integrative model of behavioral prediction in voluntary counseling of individuals with sexual high-risk behavior - Mohammad Ebrahimi; Farzad Jalilian; Hossein Ashtarian; Zahra Heidari; Fatemeh Rajati (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Voluntary counseling and testing (VCT) is one of the main efforts for the prevention of high-risk sexual behavior, including HIV/acquired immunodeficiency syndrome (AIDS). The aim of this study was to determine cognitive determinants related to voluntary counseling and HIV testing among Iranian adults based on the integrative model of behavioral prediction (IMBP). MATERIALS AND METHODS: This cross-sectional study was conducted in 2018 among Iranian adults with high-risk sexual behaviors, including drug abuse and unprotected sex, in western Iran. A total of 300 adults were randomly selected to participate voluntarily in this study. Participants filled out a self-administered questionnaire, including the background data and IMBP constructs. Data were analyzed by SPSS version 21, using statistical treatments, such as bivariate correlations, Chi-square test, t-test, and logistic regression at a 95% significant level. RESULTS: Almost 73.3% of the participants had a history of VCT. The highest probability of VCT use was in participants who were in high level of VCT skills (odds ratio: 9.635; 95% confidence interval [CI]: 3.255, 28.514]), following environmental constraints (odds ratio: 6.274; 95% CI: 2.166, 18.171). Furthermore, the IMBP constructs accounted for 85% of the variations in the outcome measure of the VCT use intention. CONCLUSIONS: Based on the result, it appears that the design and implementation of educational programs to improve upon skills and environmental constraints toward VCT use among adults with high-risk behaviors could be useful to the promotion of VCT.